Lack of Pathogenic Mutation in the Human CAII Gene in an Individual Suffering Renal Tubular Acidosis - Khatami, Saeid Reza; Galehdari, Hamid; Shariati, Gholamreza; Hamid, Mohammad; Saberi, Ali Hossein; Koorechinzade, Leila (Journal of Pediatric Nephrology, 2014)
Renal tubular acidosis (RTA) is a rare genetic disorder. It has four clinical types, and type 3 demonstrates a mixed pattern of tubular dysfunction. The causative gene for type 3 RTA (CAII) is located on the 8q22 locus and encodes a protein called carbonic anhydrase II. In this study, we analyzed the entire exons and flanking regions of the CAII gene in a child suffering renal tubular acidosis with an autosomal recessive pattern that was diagnosed with type3 RTA. DNA was extracted from the blood sample of the patient and his parents by the salting out extraction method. The exons and flanking regions of the CAII gene were amplified using polymerase chain reaction (PCR). We performed exon direct sequencing by forward and reverse primers, which were designed by primer3 program. No mutation was found following the screening of the entire coding sequence of the CAII gene. It is likely that another gene might be involved in this case. In other words, other types of RTA have to be considered. Keywords: Renal Tubular Acidosis, distal, type 3; Gene; Polymerase Chain Reaction; Sequence Analysis, DNA.